Transforming Land Conflicts in Building Peace in Urut Sewu, Kebumen Regency, Central Java - Wahyudi, Bambang (Edumaspul: Jurnal Pendidikan, 2023)
This research discusses post-land conflict transformation efforts between the AD Dislitbang and the community in Urut Sewu. Agrarian conflict is a conflict that often occurs in Indonesia. This unclear land ownership has resulted in problems between the TNI, in this case Dislitbangad, and the farming community; the TNI uses the land for training and testing heavy weapons, while the community uses the land to cultivate secondary crops. This research uses a qualitative descriptive method, where the research results show the dynamics of land conflicts in Urutsewu and efforts to transform the conflict towards peace. The results of the research show that the dynamics of conflict between the Urut Sewu Dislitbangad, Kebumen Regency can be seen from the factors causing the conflict, which are based on socio-economic aspects in the form of the community's need and dependence on agricultural land as a necessity for their life which makes the Urutsewu community use all means, including violence, to defend their agricultural land. Meanwhile, conflict transformation is a long-term peace process that includes various efforts to reconstruct new relationships, build trust, empathy and cooperation through reconciliation, and strengthen social resilience at the personal, relational, structural and cultural levels.